2020
DOI: 10.1186/s11671-020-03298-w
|View full text |Cite
|
Sign up to set email alerts
|

Organic Phosphorous and Calcium Source Induce the Synthesis of Yolk-Shell Structured Microspheres of Calcium Phosphate with High-Specific Surface Area: Application in HEL Adsorption

Abstract: Yolk-shell-structured calcium phosphate microspheres have a great potential for medical applications due to their excellent physicochemical properties and biocompatibility. However, developing a yolk-shell-structured calcium phosphate with high adsorption capability remains a challenge. Herein, a porous yolk-shell-structured microsphere (ATP-CG) of calcium phosphate with high-specific surface area [S BET = 143 m 2 g −1 , which is approximately three times as high as that of ATP-CL microspheres synthesized by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…[ 36 ] The specific surface areas of the coatings were measured via mercury intrusion experiments to quantitatively explain the degradation rate sequence. [ 37 ] The largest volume of mercury intrusion was found in the fHAP coating (0.0181 mL), followed by the cHAP coating (0.0057 mL), the cCaP coating (0.0033 mL), and the tHAP coating (0.0024 mL). This sequence was in good agreement with that of the degradation rates (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…[ 36 ] The specific surface areas of the coatings were measured via mercury intrusion experiments to quantitatively explain the degradation rate sequence. [ 37 ] The largest volume of mercury intrusion was found in the fHAP coating (0.0181 mL), followed by the cHAP coating (0.0057 mL), the cCaP coating (0.0033 mL), and the tHAP coating (0.0024 mL). This sequence was in good agreement with that of the degradation rates (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorus-containing biomolecules can regulate the mineralization process. 516 Various phosphorus-containing biomolecules were used as the organic phosphorus sources in the synthesis of a variety of calcium (or This journal is © The Royal Society of Chemistry 2024 other metal) phosphate nanostructured materials with various morphologies, including adenosine 5 0 -triphosphate, 325,[517][518][519][520][521][522][523][524][525] adenosine 5 0 -diphosphate, 526 adenosine 5 0 -monophosphate, 527 creatine phosphate, [528][529][530] cytidine-5 0 -triphosphate, 531 pyridoxal-5 0phosphate, 532,533 fructose 1,6-bisphosphate, 326,534,535 b-glycerophosphate, 536 riboflavin-5 0 -phosphate 537 and phosphoserine. 538 Conventional syntheses of calcium phosphate materials are usually realized by the direct reactions of inorganic calcium salts and inorganic phosphates in solution.…”
Section: Bioinspired Bioactive Materialsmentioning
confidence: 99%
“…Calcium phosphate (CaP) materials are highly similar to the mineral composition of bone tissue with excellent biocompatibility and osteoconductivity, which have been widely used in bone tissue engineering [ 62 , 63 ]. In recent years, researchers have found that CaP NPs possess controllable particle size [ 64 ], high specific surface area [ 65 ], mild preparation conditions [ 64 ] and pH responsiveness [ 66 ], allowing most drugs to be adsorbed via ionic crosslinking or hydrogen bonding [ 67 , 68 ], with the potential as delivery systems for bone repair therapy. For example, Zhou et al prepared HA nanospheres with high specific surface area, which significantly improved the loading efficiency of bone morphogenetic protein-2 (BMP-2) and effectively reduced its initial burst release.…”
Section: The Delivery Vehicle Of Nanomedicinementioning
confidence: 99%